Non-pharmacological Interventions for Anxiety and Depression in Adults With Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis - Davis, Suja P.; Bolin, Linda P.; Crane, Patricia B.; Crandell, Jamie (Frontiers in Psychology, 2020)
Objectives: To assess the published randomized controlled trials (RCT) of non-pharmacological interventions systematically and to synthesize the evidence of these interventions for the management of anxiety and depression in adults with inflammatory bowel disease (IBD) Background: Anxiety and depression are common symptoms in adults with IBD and can have many negative outcomes on their quality of life (QOL). Non-pharmacological interventions for anxiety and depression are important to improve the adaptive strategies of adults with IBD. Previously published reviews of non-pharmacological interventions to mitigate anxiety and depression in those with IBD have resulted in inconclusive evidence. This review is aimed to fill that gap. Design: Systematic review and meta-analysis Method: Using a PRISMA diagram, English-language RCT published were searched using combined keywords of inflammatory bowel disease, Crohn’s disease, ulcerative colitis, randomized controlled trial, anxiety, and depression. The Cochrane risk of bias tool is utilized to assess the methodological quality of each study. A meta-analysis of RCTs was conducted using Comprehensive Meta-Analysis (CMA) software. Results: The final review included ten studies. The overall risk of bias of the selected studies varied from low risk in three studies, some concerns in four of the studies, and high risk of bias in three of the studies. Interventions included cognitive-behavioral therapy, mindfulness-based therapy, breath–body- mind –workshop, guided imagery with relaxation, solution-focused therapy, yoga, and multicomponent interventions. The pooled evidence from all non-pharmacological interventions showed that these interventions significantly helped to reduce anxiety, depression and disease specific quality of life (QOL) in adults with IBD compared to control groups. However, the effect sizes are small. The pooled standardized mean difference (SMD) was - 0.28 (95% CI [-0.47, -0.09], p = 0.004) for anxiety, - 0.22 (95% CI [-0.41, -0.03], p = 0.025) for depression and 0.20 (95% CI [0.004, 0.39], p = 0.046) for disease specific QOL. Conclusion: The addressed non-pharmacological interventions were multifaceted and demonstrated positive effects on anxiety and depression, and QOL in those with IBD. Healthcare providers can facilitate a discussion with adults with IBD about the availability of these interventions to mitigate their anxiety and depression and to improve their QOL.